Grain yield responses of lowland rice varieties to increased amount of nitrogen fertilizer under tropical highland conditions in central Kenya - Symon M. Njinju; Hiroaki Samejima; Keisuke Katsura; Mayumi Kikuta; Joseph P. Gweyi-Onyango; John M. Kimani; Akira Yamauchi; Daigo Makihara (Plant Production Science, 2018)
Tropical highland conditions in Mwea Kenya, ensure the high radiation and the large day–night temperature differences. Such conditions are generally believed to promote rice growth and yield, but the current grain yield is lower than the expectation. In the current standard N fertilizer practice in Mwea, 75 kg nitrogen (N) ha−1 is applied in three splits at fixed timing. The effects of increases in N fertilizer amount (125, 175, and 225 kg N ha−1) on rice growth and yield were evaluated to test the hypothesis that unachieved high rice grain yield in Mwea is due to insufficient amount of N fertilizer. Two popular lowland varieties in Mwea (Basmati 370 and BW196) and two varieties reported as high yielding in other countries (Takanari and IR72) were used. Shoot dry weight (DW) increased with increases in the amount of N fertilizer applied in three splits at fixed timing, irrespective of variety. It reached approximately 20 t ha−1 under increased N conditions (>75 kg N ha−1) in several cases, indicating that high biomass production could be achieved by increasing N application rate. However, the increased biomass did not increase grain yield, due to decreased grain filling under high N conditions in all varieties. Thus, N amounts above 75 kg ha−1 were ineffective for increasing grain yields in Mwea, where N fertilizer was applied in three splits at fixed timing. Increasing influence of low temperature under high N conditions may be one of the reasons for the decreased grain filling in Mwea.